Low-Temperature Electrochemical Oxidation of Methane into Alcohols - Mehmood, Adeel; Chae, Sang Youn; Park, Eun Duck (Catalysts, 2024)
The direct oxidation of methane to methanol is considered challenging due to the intrinsically low reactivity of the C–H bond of methane and the formation of a large number of unstable intermediates (methanol, formaldehyde, and formic acid) relative to the yield of methane. However, promising advances have recently been reported in this area based on the use of electrochemical systems that differ from traditional thermal catalysis. In this review, the recent advances in direct and indirect electrochemical methane conversion with homogeneous catalysts are reviewed and discussed, especially under low-temperature conditions. Finally, the limitations of the current electrochemical methane conversion technology and future research directions are discussed.
Keywords: electrocatalyst; electrochemistry; methane; methanol; selective oxidation